PERTARUNGAN WACANA POLITIK HUKUM ISLAM dI INdONESIA - Hafidh, Ahmad (Yustisia, 2014)
Politic of law is a result of social, political, and cultural dynamics that is life and increase. It is not merely a value-free policy formulation, but the product of a process of interests between groups within a country, in addition to the influence of history, philosophy, and the characteristics of life embraced. Likewise Negara Kesatuan Republik Indonesia (NKRI), each phase of the history of national life have generated legal policy as a result of the intersection of social, political, cultural and even economic interests played by the various political components of the nation. Conceptual disputes, exchange of interests, and the various dynamics that in the terminology of sociological studies interpreted as a championship make   a domination and hegemony of discourse so that produce the national policy. This article describes a sketch of the history of politic of law of Indonesia in relation to the Islamic sharia from pre-proclamation of independence periodof Indonesia Republic to the post-reform. Inexplaining the reason, this paper uses the symbolic power championship theoretical framework developed by sociologist Pierre Boudieu. In the theory, Pierre Boudieu mention that the sphere of social life is a struggle between the modals of the group to control a discourse. In order to win the champion often the violence occurred. Depend on the domination of doxa (symbolic power), the faction of political power dominate the policy, character and style of social life was, of course, including the legal sphere. In the span of the history of Indonesia, determination of political factors in control of politic of national laws related to Islamic sharia is very powerful. Even Islamic shariah in several phases be used as a tool of government to control the social dynamics for the interests of power.